Ethnoveterinary medicines for cattle (Bos indicus) in Bulamogi county, Uganda: plant species and mode of use - Tabuti, John R.S.; Dhillion, Shivcharn S.; Lye, Kaare A. (Journal of Ethnopharmacology, 2003)
In this paper, we present an inventory and the mode of use of plants to treat cattle. This study was carried out in Bulamogi county of Uganda, using methods consisting of semi-structured interviews employing a checklist of questions, questionnaires, direct observations, and biological inventories. Farmers employ both traditional and western medicine to treat their animals. The local people identified 33 different diseases, and had herbal treatments for nine of these. Some of the diseases mentioned by farmers indicated symptoms of diseases. Thus, the naming of diseases by local people when compared to the western veterinary medicine system, at times did not distinguish between diseases and symptoms of diseases. This is because the local disease nomenclature is based on symptoms of diseases, whereas under western veterinary science diseases are named according to aetiological information. As for traditional medicine, we report for the first time the use of 38 plant species, distributed in 37 genera and 28 families, to treat the common cattle diseases in Bulamogi. Most of these plants grow wild (76.3%), are indigenous (68.4%) and are shrubs (60.5%). The plant parts most frequently used for treating cattle are roots (37.5%) and leaves (27.5%). Medications are mostly prepared as infusions and seldom as decoctions. Topical application of some medicines is practised as well. The species used to treat cattle are also used to treat some human ailments and have some other uses as well. Most of the curative species reported here are directed at treating East Coast fever (ECF), a disease known to cause high fatalities in cattle.
Keywords: Ethnoveterinary medicine; Cattle diseases; Traditional knowledge; Uganda; Conservation